Uptake of uranium by lettuce (Lactuca sativa L.) in natural uranium contaminated soils in order to assess chemical risk for consumers - Neves, O. (2013)
Uranium mining activity in Cunha Baixa (Portugal) village has left a legacy of polluted soils and irrigation water. A controlled field experiment was conducted with lettuce (Lactuca sativa L.) in an agricultural area nearby the abandoned mine in order to evaluate uranium uptake and distribution in roots and leaves as well as ascertain levels of uranium intake by the local inhabitants from plant consuming. Two soils with different average uranium content (38 and 106 mg/kg) were irrigated with non-contaminated and uranium contaminated water (<20 and >100 μg/l). A non-contaminated soil irrigated with local tap water (<1 μg/l uranium) was also used as a control. Uranium in lettuce tissues was positively correlated with soil uranium content, but non-significant differences were obtained from contaminated soils irrigated with different water quality. Uranium in plants (dry weight) growing in contaminated soils ranged from 0.95 to 6 mg/kg in roots and 0.32 to 2.6 mg/kg in leaves. Lettuce bioconcentration is more related to available uranium species in water than to its uranium concentration. Translocated uranium to lettuce leaves corresponds to 30% of the uranium uptake whatever the soil or irrigation water quality. A maximum uranium daily intake of 0.06 to 0.12 μg/kg bodyweight day was estimated for an adult assuming 30 to 60 g/day of lettuce is consumed. Although this value accounts for only 10% to 20% of the recommended Tolerable Daily Intake for ingested uranium, it still provides an additional source of the element in the local inhabitants’ diet